"I know what you're going to ask me" Why respondents don't read survey questions. (July 2019) - Brosnan, Kylie; Babakhani, Nazila; Dolnicar, Sara
Tracking respondents' eyes while they complete a survey reveals that (a) they do not read instructions, survey questions, and answer options carefully enough, investing only as little as 32% of the required time; (b) their attention diminishes over the course of the survey; and (c) their self-reports of the survey experience do not reflect actual survey completion behavior. As much as 15% of survey data may be negatively affected by systematic respondent inattention. From these findings, we derive practical recommendations on how to improve pre-testing of surveys and how to reduce the likelihood of survey respondents ignoring instructions and not reading survey questions and answer options.